Pengaruh Pemberian Jus Daun Torbangun Dengan Peningkatan Produksi ASI Pada Ibu Nifas Di PMB Ny. N Kota Bekasi Tahun 2023 - Aisyah, Yeki Supriaten (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Background: In exclusive breastfeeding, 349,968 infants aged 0-6 months out of 754,438 infants aged 0-6 months (46.4%) this figure is still below the National coverage of 52.3%, especially the National target of 80%. This problem can be reduced by giving torbangun leaf juice so that nursing mothers give breast milk to their babies at least until the age of 6 months. The mechanism of torbangun leaves in increasing milk production is by increasing the proliferation of breast glandular cells in secreting milk. West Java Health Department Data 2020. Objective: This research aims to find out the analysis of the effect of giving Torbangun leaf juice by increasing breast milk expenditure in breastfeeding mothers at the PMB in Bekasi city.. Methodology: The type and method of this research is quantitative research using quasy experimental designs. The sample in this study amounted to 20 nursing mothers. Research instrument with checklist sheet about increasing breastmilk expenditure in infants 0-3 days and breastmilk pump. This checklist sheet has been tested for validity. Data were analyzed using paired T-Test, obtained p-value of 0,000. Research Results: The results showed the average volume of breast milk before being given torbangun leaf juice was 3.35 cc, the average volume of breast milk after being given torbangun leaf juice post test one day was 36.50 cc, the average volume of breast milk after being given juice torbangun leaf post test the second day was 71.00 cc, and the average volume of breast milk after being given juice the third day post torbangun leaf was 108.25 cc which means an increase in breast milk expenditure. Paired T-Test test results obtained p-value of 0,000. Conclusions and suggestions: torbangun leaf juice can increase milk production in nursing mothers 0-3 days. The results of this study can be used as an alternative to increase milk production and as a reference for further research.